2014
DOI: 10.1155/2014/528650
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent System for Identifying Acetylated Lysine on Histones and Nonhistone Proteins

Abstract: Lysine acetylation is an important and ubiquitous posttranslational modification conserved in prokaryotes and eukaryotes. This process, which is dynamically and temporally regulated by histone acetyltransferases and deacetylases, is crucial for numerous essential biological processes such as transcriptional regulation, cellular signaling, and stress response. Since the experimental identification of lysine acetylation sites within proteins is time-consuming and laboratory-intensive, several computational appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Maximal dependence decomposition (MDD) [31] was utilized to cluster all fragment sequences into subgroups in order to detect those motifs that were statistically conserved among largescale sequence data. The clustering method was performed using MDDLogo [15], which has been demonstrated to increase the effectiveness of PTM sites identification by dividing a group of protein sequences into smaller subgroups before performing the computational identification of the PTM sites [21,[34][35][36][37][38][39][40][41][42][43][44]. In this investigation, a chi-square test χ 2 (A i , A j ) was used to iteratively evaluate the interdependence between two positions, A i and A j , which are flanking the substrate site, based on the occurrence of amino acids.…”
Section: Detection Of Motif Signatures By Maximal Dependence Decomposmentioning
confidence: 99%
“…Maximal dependence decomposition (MDD) [31] was utilized to cluster all fragment sequences into subgroups in order to detect those motifs that were statistically conserved among largescale sequence data. The clustering method was performed using MDDLogo [15], which has been demonstrated to increase the effectiveness of PTM sites identification by dividing a group of protein sequences into smaller subgroups before performing the computational identification of the PTM sites [21,[34][35][36][37][38][39][40][41][42][43][44]. In this investigation, a chi-square test χ 2 (A i , A j ) was used to iteratively evaluate the interdependence between two positions, A i and A j , which are flanking the substrate site, based on the occurrence of amino acids.…”
Section: Detection Of Motif Signatures By Maximal Dependence Decomposmentioning
confidence: 99%
“…This modification is found widely in eukaryotic cells and occurs during the physiological activities at various stages (Kimura et al, 2005;Ishfaq et al, 2012;Lu et al, 2014), from regulating the function of proteins, especially in terms of protein stability (Zhou et al, 2016), to intracellular signal transduction (Batta et al, 2007;Tang et al, 2007;Spange et al, 2009), disease and other physiological processes (Batta et al, 2007;Iyer et al, 2012;Marouco et al, 2013;Ye et al, 2017). Acetylation occurs on the ε-amino group of lysine residues (Lu et al, 2014). As a highly reversible protein modification process, acetylation is regulated by the action of histone acetylase and histone deacetylase (Guarente, 2011;Qian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although over 58,000 acetylation sites have been characterized in prokaryotic and eukaryotic species, the regulatory HATs of most of these sites still remain to be elucidated. Previously, we and others developed about 15 computational programs to predict general acetylation sites from protein sequences, with a satisfying accuracy716171819202122232425262728293031. However, the prediction of HAT-specific acetylation sites was still unavailable until the release of ASEB1132, which clearly demonstrated that different types of HATs could modify distinct protein substrates1132.…”
Section: Discussionmentioning
confidence: 99%
“…compiled a much larger training data set with 3,600 human lysine acetylation sites from a large-scale study7, and adopted the support vector machines (SVMs) algorithm to predict acetylation sites18. To date, there have been at least a dozen of additional computational programs constructed for the accurate prediction of general lysine acetylation sites, such as LysAcet19, N-Ace20, EnsemblePail21, BPBPHKA22, PLMLA2324, PSKAcePred25, KAcePred26, LAceP27, SSPKA28, AceK29, iPTM-mLys30 and KA-predictor31. However, none of them can predict HAT-specific sites.…”
mentioning
confidence: 99%